2021
DOI: 10.1002/celc.202001504
|View full text |Cite|
|
Sign up to set email alerts
|

Syngas Production from Electrochemical CO2 Reduction on Copper Oxide Electrodes in Aqueous Solution

Abstract: Electrochemical CO2 reduction to value‐added chemicals and fuels using renewable energy represents a promising strategy for reducing CO2 emissions and achieving effective energy storage. In this work, nano‐sized CuO catalysts were prepared by using the homogeneous precipitation method for electrochemical CO2 reduction to CO. The CO2 reduction studies combined with the characterization results show that structure‐activity relationships of the CuO catalysts depend on the calcination temperature. The as‐synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Yao et al reported that the CuO nanostructure would be partially reduced to Cu 2 O and metallic Cu during electrochemical CO 2 reduction to syngas. A comparison of the surface chemical compositions of the fresh and spent CuO catalysts indicated that the conversion of Cu­(II) to Cu­(I) and Cu(0) would result in the increase in OV content by about 10% . In other words, the partial oxidation of Cu­(I) to Cu­(II) might give rise to the decrease in OVs accordingly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yao et al reported that the CuO nanostructure would be partially reduced to Cu 2 O and metallic Cu during electrochemical CO 2 reduction to syngas. A comparison of the surface chemical compositions of the fresh and spent CuO catalysts indicated that the conversion of Cu­(II) to Cu­(I) and Cu(0) would result in the increase in OV content by about 10% . In other words, the partial oxidation of Cu­(I) to Cu­(II) might give rise to the decrease in OVs accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…The capacitive currents (Δ j ) against the scanning rate were then plotted and the C dl was calculated as the slope of the fitting line (as shown in eq ). ECSA was then calculated by dividing the C dl by the capacitance of ideal Cu 2 O with a smooth surface (usually taken as 40 μF/cm 2 in the alkaline electrolyte). , The specific method for calculating ECSA is shown in eq . The ECSA-normalized current density is then calculated to reflect the specific intrinsic activity, as shown in eq .…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, as particle size of CuO catalyst increased, the selectivity towards CO and H 2 production slightly decreased, while the CO 2 RR selectivity to methanol and ethanol increased. This had been associated with the particle size effect, since the increased particle size had caused the decrease in the density of the undercoordinated sites (Yao et al, 2021).…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Thus, researching the ion movement in the electrochemical process will provide a theoretical basis for the electrochemical assembly of micro-and nanoscale novel materials, which can realize the application of many functional devices. An excellent photothermal device often has the characteristics of micro–nano structures, mainly concentrated between 10 nm and 500 μm. CuO is one of the promising photothermal materials because of its high light absorption and good solar selectivity. It can be prepared by simple in situ oxidation and sintering of copper metal. The fractal dendrite structure, mimicking the natural trees and ferns, has a micro-/nanoscale hierarchical structure, a larger surface area, and a light cage effect, which may further improve the photothermal performance. …”
Section: Introductionmentioning
confidence: 99%